Cervinotaptera guilberti n.gen., n. sp. a conspicuous apterous Mezirinae from Madagascar (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Marchal, Lorène (Zootaxa, 2012)
Nine genera and 19 species of apterous Mezirinae are recorded to date from Madagascar (Heiss 2012), all of them endemic. Cervinotaptera guilberti n. gen., n. sp. differs from all of them by the presence of two distinct thoracic evaporation structures and the horn of a stag-like process on pronotum.